Gut-brain axis in adolescent depression: a systematic review of psychological implications and behavioral interventions - Liu, Haitao; Li, Xiaoli; Shi, Ying; Hong, Ke; Wang, Xing; Huang, Congfu (Frontiers in Nutrition, 2025)
BackgroundAdolescent depression affects 13% of youths globally, with 30–40% exhibiting treatment resistance. Emerging evidence implicates gut microbiome dysbiosis in core behavioral symptoms (e.g., anhedonia, social withdrawal) via gut-brain axis (GBA) pathways. This systematic review synthesizes clinical and preclinical evidence (2014–2025) to delineate the microbiota-behavior interactions and evaluate microbiome-targeted interventions.MethodsFollowing PRISMA 2020 guidelines, 45 studies (29 clinical trials, 11 animal models, 5 meta-analyses) were analyzed from PubMed, Web of Science, and Embase. Data extraction focused on microbiome composition, neurobehavioral outcomes, and intervention efficacy. Random-effects meta-analyses pooled effect sizes (95% CIs).ResultsDepressed adolescents showed reduced gut microbiota α-diversity (Shannon index SMD = −0.92; 95% CI: −1.24, −0.60) and altered taxa abundance (e.g., Bacteroidetes depletion: Δ = −32%). Dysbiosis correlated with anhedonia severity (r = 0.42; 95% CI: 0.28, 0.55) and impaired social functioning. Psychobiotics (e.g., Lactobacillus plantarum PS128) significantly reduced depressive symptoms (HAM-D Δ = −4.2; 95% CI: −5.1, −3.3) vs. placebo and improved emotion recognition (+18%; 95% CI: 2.1, 33.9). Sex-specific effects were prominent: Bifidobacterium breve enhanced reward responsiveness in females (SMD = 0.61; 95% CI: 0.22, 1.00). Current data lack large-scale RCTs for fecal microbiota transplantation (FMT) in adolescents.ConclusionGut microbiome modulation shows promise as an adjunct to behavioral therapies (e.g., CBT). Bifidobacterium breve’s female-predominant effects suggest hormonal modulation. Future research must address gaps in FMT safety, developmental mechanisms, personalized nutritional interventions.